Conjunction saves multiple sluicing: How *(and) why?. Issue 1 (15th September 2020) - Citko, Barbara; Gračanin-Yuksek, Martina
Abstract : Our goal in this paper is to analyze coordinated wh-sluicing in English and compare its properties to the properties of multiple sluicing, coordinated wh-questions and coordinated clefts. We show that none of these constructions has the properties of coordinated sluices, and conclude that coordinated sluices are not derivationally related to them. We propose, instead, that coordinated sluices underlyingly involve coordination of two interrogative CPs with a single fronted wh-phrase and an elided TP in each CP. In addition, we propose that the elided TP of the second conjunct in a coordinated sluice contains a pronominal element (an E-type pronoun) coindexed with the trace of the fronted wh-phrase in the first conjunct. We show that this analysis derives the properties of coordinated sluices and explains why they differ from multiple sluices, coordinated wh-questions and coordinated clefts.